5-Aminolevulinic Acid and Contrast-Enhanced Ultrasound: The Combination of the Two Techniques to Optimize the Extent of Resection in Glioblastoma Surgery. Issue 6 (18th March 2020) - Della Pepa, Giuseppe Maria; Ius, Tamara; La Rocca, Giuseppe; Gaudino, Simona; Isola, Miriam; Pignotti, Fabrizio; Rapisarda, Alessandro; Mazzucchi, Edoardo; Giordano, Carolina; Dragonetti, Valentino; Chiesa, Silvia; Balducci, Mario; et al.
Abstract: BACKGROUND: The survival benefit in maximizing resection in glioblastomas (GBMs) has been demonstrated by numerous studies. The true limit of infiltration of GBMs has been an overwhelming obstacle, and several technological advances have been introduced to improve the identification of residual tumors. OBJECTIVE: To evaluate whether the integration of 5-aminolevulinic acid (5-ALA) with microbubble contrast-enhanced ultrasound (CEUS) improves residual tumor identification and has an impact on the extent of resection (EOR), overall survival (OS), and progression-free survival (PFS). METHODS: A total of 230 GBM procedures were retrospectively studied. Cases were stratified according to the surgical procedure into 4 groups: 5-ALA- and CEUS-guided surgeries, 5-ALA-guided surgeries, CEUS-guided surgeries, and conventional microsurgical procedures. RESULTS: Patients undergoing conventional microsurgical procedures showed the worst EORs compared to the assisted techniques (5-ALA and CEUS procedures). Both 5-ALA and CEUS techniques improved the EOR compared to conventional microsurgical procedures. However, their combination gave the best results in terms of the EOR ( P  = .0003). The median EOR% and the number of supramarginal resections are hence superior in the 5-ALA + CEUS + group compared to the others; this observation had consequences on PFS and OS in our series. CONCLUSION: In terms of the EOR, the best results can be achieved through a combination of both techniques, where the 5-ALA-guided procedure is followed by a final survey with CEUS. Compared with other intraoperative imaging techniques, CEUS is a real-time, readily repeatable, safe, and inexpensive technique that provides valuable information to the surgeon before, during, and after resection. Graphical Abstract: